Management of blast disease of finger millet (Eleusine coracana) through fungicides, bioagents and varietal mixture - KUMAR*, BIJENDER; KUMAR, J. (Indian Phytopathology, 2011)
Studies were conducted during kharif 2006 and 2007 for the management of blast disease of finger millet throughfungicides, bioagents and varietal mixtures. Results revealed that seed treatment with Pseudomonas fluorescens Pf 2 (@ 0.6%)Â + its two foliar sprays (@ 0.6%) followed by two sprays of hinosan @ 0.1% were significantly most effective in reducing blastÂ disease. The treatments provided 81.69 and 77.72 per cent yield increase over the control, respectively. In order to extend theÂ life span of VL 149 (resistant variety) as well as reduce blast damage in the local, but preferred variety, the varieties were sownÂ in different combinations. Results revealed that the 1:1 mixture of PRM 1 (V1) and VL 149 (V2) varieties, was best, whereinÂ incidence of neck blast (0.84%) and finger blast (10.42%) diseases was lesser than both the varieties, individually. The treatmentÂ provided 96.48 and 94.14 per cent neck blast control over V1 and V2 varieties, respectively, while, it provided 80.06 and 69.52 perÂ cent finger blast control over V1 and V2 varieties, respectively. In addition to disease control the treatment also increased theÂ yield by 36.56 and 19.51 per cent over V1 and V2 varieties, respectively.